Toward high-throughput engineering techniques for improving CAR intracellular signaling domains - Butler, Savannah E.; Hartman, Colin J.; Huang, Yina H.; Ackerman, Margaret E. (Frontiers in Bioengineering and Biotechnology, 2023)
Chimeric antigen receptors (CAR) are generated by linking extracellular antigen recognition domains with one or more intracellular signaling domains derived from the T-cell receptor complex or various co-stimulatory receptors. The choice and relative positioning of signaling domains help to determine CAR T-cell activity and fate in vivo. While prior studies have focused on optimizing signaling power through combinatorial investigation of native intracellular signaling domains in modular fashion, few have investigated the prospect of sequence engineering within domains. Here, we sought to develop a novel in situ screening method that could permit deployment of directed evolution approaches to identify intracellular domain variants that drive selective induction of transcription factors. To accomplish this goal, we evaluated a screening approach based on the activation of a human NF-κB and NFAT reporter T-cell line for the isolation of mutations that directly impact T cell activation in vitro. As a proof-of-concept, a model library of CAR signaling domain variants was constructed and used to demonstrate the ability to discern amongst CARs containing different co-stimulatory domains. A rare, higher-signaling variant with frequency as low as 1 in 1000 could be identified in a high throughput setting. Collectively, this work highlights both prospects and limitations of novel mammalian display methods for CAR signaling domain discovery and points to potential strategies for future CAR development.